Natural orifice transvaginal endoscopic surgery for endometrial cancer - Chyi-Long Lee; Kai-Yun Wu; Fang-Ying Tsao; Chen-Ying Huang; Chien-Min Han; Chih-Feng Yen; Kuan-Gen Huang (Wolters Kluwer Medknow Publications, 2014)
Objective: This study was conducted to describe the feasibility of treating endometrial cancer with hysterectomy, bilateral salpingo-oophorectomy, and bilateral pelvic lymphadenectomy by natural orifice transluminal endoscopic surgery (NOTES). Methods: Women with early-stage endometrial cancer underwent surgical staging by transvaginal NOTES in a tertiary referral medical center, and surgical outcomes were measured. Results: Three patients with a mean age of 46.3 [standard deviation (SD) = 2.5] years and a body mass index of 27.7 (SD, 2.4) kg/m2 were selected. The average operative time was 249.3 (SD, 49.3) minutes. All patients had minimal blood loss during the operation (<50 mL) without intraoperative blood transfusion. All of them had a surgical staging of pT1aN0M0 and FIGO IA. No intraoperative or postoperative complications were noted. No cases were converted to traditional laparoscopy or laparotomy. Conclusion: NOTES is a minimally invasive surgery and leaves only invisible scars. Our preliminary results showed the safety and feasibility of transvaginal NOTES in staging surgery for early-stage endometrial cancer. However, it should be evaluated in more cases.